Long-term sulfuric and hydrochloric acid resistance of silica fume and colemanite waste reinforced metakaolin-based geopolymers - Aygormez, Yurdakul; Canpolat, Orhan (PONTIFICIA UNIV CATOLICA CHILE, ESCUELA CONSTRUCCION CIVIL, 2021)
For this paper, silica fume (SF), slag (S), and colemanite waste (C) were added to metakaolin (MK)-based geopolymer composites and exposed to 10% (by volume) hydrochloric acid (HCl) and sulfuric acid (H2SO4) solutions for up to 12 months. Geopolymer composites were examined in terms of weight loss, compressive strength, and flexural strength at 3, 6, and 12 months in solutions. Furthermore, Scanning Electron Microscopy (SEM), Micro computed Tomography (micro-CT), Fourier Transform Infrared Spectroscopy (FTIR), and X-ray Diffraction (XRD) analyses were carried out to examine the microstructure before and after acid attacks. An important decrease in flexural and compressive strengths was seen when geopolymer mortars were subjected to sulfuric and hydrochloric acid attacks. The main cause of this situation is the deterioration of the oxy-aluminum bridge (-Al-Si-O) when exposed to sulfuric and hydrochloric acid. The oxy-aluminum bridge (-Al-Si-O), the primary factor in the geopolymer matrix, plays a significant role in consolidating the gel and enhancing the bond formed between the matrix components. Despite this, geopolymer mortar samples maintain the aluminosilicate structure. Compared to hydrochloric acid, sulfuric acid is a stronger solution, resulting in a greater loss of compressive and flexural strengths.
Keywords: geopolymer; metakaolin; colemanite waste; silica fume; sulfuric acid; hydrochloric acid; FLY-ASH; COMPRESSIVE STRENGTH; CHEMICAL DURABILITY; ALKALI ACTIVATION; SODIUM-SILICATE; BOTTOM ASH; CONCRETE; PERFORMANCE; SULFATE; MORTARS; Construction & Building Technology; Engineering